2003
DOI: 10.1084/jem.20022031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intramolecular Epitope Spreading in the Pathogenesis of Endemic Pemphigus Foliaceus (Fogo Selvagem)

Abstract: We report here a relationship between intramolecular epitope spreading and the clinical onset of the endemic form of pemphigus foliaceus in a Brazilian community with a high prevalence and incidence of the disease. Also known as Fogo Selvagem (FS), this disease is characterized by severe skin blistering and pathogenic anti–desmoglein-1 (Dsg1) autoantibodies. These autoantibodies bind the Dsg1 ectodomain and trigger keratinocyte cell detachment, the hallmark of FS. We show that (a) sera from FS patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
194
3
11

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(220 citation statements)
references
References 36 publications
12
194
3
11
Order By: Relevance
“…Individuals who later developed fogo selvagem, an endemic variant of PF, were found to exhibit autoAb against nonpathogenic epitopes of Dsg1 in the preclinical stage. Once full-blown disease occurred, they had developed autoAb directed against a distant, pathogenic epitope of the ECD1 of Dsg1 (36). There is also evidence for intermolecular epitope spreading in pemphigus since patients with PV may develop PF later in the course of disease (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who later developed fogo selvagem, an endemic variant of PF, were found to exhibit autoAb against nonpathogenic epitopes of Dsg1 in the preclinical stage. Once full-blown disease occurred, they had developed autoAb directed against a distant, pathogenic epitope of the ECD1 of Dsg1 (36). There is also evidence for intermolecular epitope spreading in pemphigus since patients with PV may develop PF later in the course of disease (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that intramolecular epitope spreading of Dsg3 T cell peptides does not occur once the disease is clinically apparent since there was no direct relationship between Dsg3 peptide reactivity and a distinct clinical phenotype (i.e., active vs remittent disease). A recent study (36) clearly demonstrated that epitope spreading occurs in pemphigus foliaceus (PF), a related autoimmune disorder associated with autoAb against Dsg1. Individuals who later developed fogo selvagem, an endemic variant of PF, were found to exhibit autoAb against nonpathogenic epitopes of Dsg1 in the preclinical stage.…”
Section: Discussionmentioning
confidence: 99%
“…Several characteristics of autoantibodies have been as-sociated with pathogenicity. In pemphigus vulgaris, a skin disease, reactivity to different desmoglein epitopes is associated with different disease outcomes (3). In antibody-mediated models of arthritis in mice, a combination of antibodies with different fine specificities and isotypes was found to be more efficient than a single antibody in inducing disease (4,5).…”
mentioning
confidence: 99%
“…No caso do PFE, o epitope spreading intramolecular poderia justificar a presença de auto-anticorpos em indivíduos sadios que vivem em áreas endêmicas e que não desenvolvem a enfermidade. 26,27 Os indiví-duos normais de áreas endêmicas exibem auto-anticorpos que reconhecem porções não patogênicas da Dsg1, o ectodomínio 5 (EC5). A produção de anticorpos antiEC5 seria desencadeada por reação cruzada de antígenos exógenos com homologia de seqüência com o domínio EC5 da Dsg1.…”
Section: Epitope Spreading Intramolecular (Intraproteína) Pênfigo Vulgarunclassified
“…A produção de anticorpos antiEC5 seria desencadeada por reação cruzada de antígenos exógenos com homologia de seqüência com o domínio EC5 da Dsg1. Caso os indivíduos apresentem a seqüência de alelos no HLADRB1 e recebam estímulo ambiental capaz de deflagrar o reconhecimento das porções patogênicas (EC1 e EC2) da Dsg1, instala-se o PFE [27][28][29] (Figura 3). Em indivíduos expostos repetidamente à picada de insetos hematófagos e com predisposição genética ao FS, o epitope spreading exacerba a resposta imunológica [27][28][29] e aumenta a produção de anticorpos patogênicos da subclasse IgG4 que reconhecem os EC1 e EC2 da Dsg1.…”
Section: Epitope Spreading Intramolecular (Intraproteína) Pênfigo Vulgarunclassified